Analisis Ayat Tarbawi Dalam KMA Nomor 183 Tahun 2019 Mata Pelajaran Al-Qur’an Hadis di Madrasah Aliyah - Siti Rohmah; Diah Mutiara; Oneng Nurul Badriyah; Faris Rahmat Hidayat (STIT Muslim Asia Afrika, 2022)
The purpose of this study was to find out the Tarbawi verse in KMA number 183 of 2019 on the Al-Qur’an Hadith subject matter at Madrasah Aliyah. This study uses a qualitative approach. The method used is the method of literature (library research). The research focuses on the study of literature on the analysis of the verses of tarbawi in KMA number 183 of 2019. In accordance with the main issues discussed, this research begins with an efforts to classify the verses of tarbawi in KMA number 183 of 2019 in the subject Al-Qur’an Hadith subjects at Madrasah Aliyah. For this purpose, two sources of data were: 1) primary data, namely data obtained from the Quran and KMA number 183 of 2019. 2) Secondary data is a source of support and complement to primary data, such as books, journals related to verses of tarbawi, and various other related sources with a research problem. The results of this study indicate that the tarbawi verses in KMA number 183 of 2019 the Al-qur’an Hadith subject at the Madrasah Aliyah are divided into two, namely first, the tarbawi verses in the Alquran Hadith subject at Madrasah Aliyah specializes in science, social studies, and language there are 18 verses. Secondly, the tarbawi verses in the Alquran Hadith subject at Madrasah Aliyah specializes in religious there are 23 verses.